Systematic literature review on factors influencing teacher motivation - Rothinam, Nirumala; Samuel, Samikkanu Jabamoney Ishak; Vengasalem, Ramachandran; Naidu, Sivabala (Edelweiss Applied Science and Technology, 2024)
Teacher motivation is one of the most influential factors that affect educational results and have a direct impact on the teachers themselves as well as the students. The purpose of this systematic review is to synthesize the findings of empirical work on teacher motivation drawing only literature that was published between the years 2000 and 2024. The study was designed with the help of the PRISMA 2020 guidelines to ensure that we capture all the possible studies related to the topic of interest and, finally, included 65 articles that met the eligibility criteria. The analysis of these researches shows that the teacher motivation is a complex package of intrinsic and extrinsic factors. Of the most important aspect is self-efficacy as a perception of a teacher’s ability to succeed, besides job satisfaction which includes teacher’s satisfaction with different features of their work. The findings of this review have significant implications to the formulation of policies and strategies in education. Therefore, policies that are put in place to increase motivation of the teaching workforce will see the staff become more committed and productive and consequently enhancing the quality of education given to the learners. The results of this study support the need to shift the emphasis to improving the educational context with a view of raising motivation of teachers.